Comparative study of gait parameters of patients undergoing distal femoral resections with non-operated and healthy limbs: a meta-analysis study - Banskota, Nishant; Fang, Xiang; Yuan, Dechao; Zhang, Wenli; Duan, Hong (Frontiers in Oncology, 2023)
Introduction: Gait analysis is one of the most important components of functional outcome evaluation in patients with lower extremity tumors. Disparities between operated limbs when compared with non-operated limbs and healthy populations based on gait parameters have merely been studied. In the present study, we attempted to analyze the gait difference and their impacts on daily life.The Gait parameters of distal femur tumor resected patients were collected from PUBMED, CNKI, MEDLINE, EMBASE, the Cochrane Database, and Google Scholar till September 30, 2022, by strictly following the inclusion and exclusion criteria. Differences between gait parameters in the operated and non-operated limbs or healthy limbs in distal femur tumor patients were analyzed based on stance phase, swing phase, cadence, and velocity. The fixed effects and a random-effects model were used to conduct a meta-analysis.Results: Six studies were included according to the selection criteria. There were 224 patients in total in these studies. Standard mean differences were calculated for all of our outcomes. Our results showed that there was a minimal difference in the standard mean difference of gait parameters between operated and non-operated limbs and healthy limbs.Conclusions: Distal femur tumor resections have been associated with deficient muscle function and strength, and impaired gait parameters. Minimal differences in the gait parameters highlighted the advantage of distal femur resection when replaced with prosthesis.